In silico, 6lu7 protein inhibition using dihydroxy-3-phenyl coumarin derivatives for SARS-CoV-2 - Özdemir, Mücahit; Köksoy, Baybars; Ceyhan, Deniz; Bulut, Mustafa; Yalcin, B. (Turkish Chemical Society, 2020)
The new emerging coronavirus (SARS-CoV-2) has become a global health problem with very rapid transmission from person to person, causing severe acute respiratory problems. In the circumstance, the discovery of vaccines or drugs to eradicate or reduce the impact of the COVID-19 has made it imperative to develop new approaches. In the current situation, many drugs on the drug bank have been researched computationally, and there has not been an emphasis on synthetic effort. We tested 42 coumarin derivatives (1a-14c) containing 14 different substituents, which are secondary metabolites of plants, and the anticoagulant Coumadin (warfarin) drug as a reference by Molecular Docking calculation technique on 6LU7 main protease of the coronavirus. Optimized geometries, electron motions and energy values of all coumarins were also determined using the Density Functional Theory (DFT) method. The drug properties of coumarins were estimated using the ADME-Tox test method. Coumarins formed strong interactions with HIS41, CYS145, and other amino acids in the active site of the main protease. In general, 6,7-dihydroxy-3-phenylcoumarin derivatives gave relatively higher scores, and for all coumarins, biphenyl (for 10a,-8.6 kcal/mol; 10b,-8.3 kcal/mol; 10c,-7.9 kcal/mol) and 4-trifluoromethylphenyl (for 13a,-8.1 kcal/mol; 13b,-8.1 kcal/mol; 13c-8.3 kcal/mol) substituted coumarin had the highest score. The coumarins data reported in this study serves as a stepping stone for in vitro and in vivo experimental research for vaccine development purposes. © 2020 Elsevier B.V., All rights reserved.
Keywords: Coumarins; COVID-19 main protease; Drug design; Molecular docking; SARS-CoV-2